Hubungan Perilaku Merokok Dengan Kejadian Tuberkulosis Paru Di Kecamatan Juntinyuat Kabupaten Indramayu - Setiawan, Dede (Afiasi : Jurnal Kesehatan Masyarakat, 2025)
Pulmonary tuberculosis (TB) is a contagious infectious disease that remains a serious public health challenge in Indonesia, including in the Juntinyuat Community Health Center (UPTD) in Indramayu Regency. Smoking is a risk factor for pulmonary TB. Exposure to cigarette smoke can disrupt respiratory function and weaken lung immunity, making it easier for Mycobacterium tuberculosis bacteria to enter and grow. This study is a quantitative study with an observational analytical design using a cross-sectional approach. The sampling technique used was total sampling with 56 respondents. Based on an analysis of 56 respondents, a statistically significant relationship was found between smoking behavior and the incidence of pulmonary tuberculosis, with a p-value of 0.000 (p < 0.05). Statistically, it can be concluded that smoking has a significant relationship to incidence of pulmonary tuberculosis. Health workers are expected to provide ongoing education about the dangers of smoking, particularly regarding its impact on increasing the risk of pulmonary tuberculosis in the community.